HUBUNGAN POLA ASUH ORANGTUA TERHADAP PERILAKU SEKSUAL PADA REMAJA DI KELURAHAN X HUBUNGAN POLA ASUH ORANGTUA TERHADAP PERILAKU SEKSUAL PADA REMAJA DI KELURAHAN X - Susilawati; Tantri Wenny Sitanggang; Mutia Isma Priselin (Jurnal Kesehatan STIKes IMC Bintaro, 2022)
Introduction sexual behavior among adolescents in Indonesia every year, this is due to several factors. One of them is parenting style. The purpose of this study was to determine the relationship between parenting and sexual behavior among adolescents aged 16-18 years in X village in 2020. The methodology of this study is a quantitative study using analytical survey research methods using research design cross-sectional. Respondents consisted of 76 adolescents with a sampling technique, namely quota sampling. Collecting data in this study using a questionnaire. The results of study this using the test Chi square, most respondents have a pattern Democratic parenting (56; 73.7%), and sexual behavior not at risk (57; 75.0%). There is a relationship between parenting and parenting sexual behavior (p = 0.000). Conclusion Democratic parenting can reducing risky sexual behavior in adolescents is expected that adolescents can communicate well with their parents about sexuality education in preventing sexual behavior in adolescents. Suggestions with the results of this study are expected to provide information and input for managers in X Village in order to improve parenting styles for sexual behavior among adolescents.